2020
DOI: 10.1111/ppc.12433
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between heart rate variability and aggressive behavior among patients with schizophrenia hospitalized in acute wards

Abstract: Purpose: To explore the state of mental treatment, heart rate variability (HRV), level of aggressive behavior, and their relationships among hospitalized patients with schizophrenia.Design and Methods: This study adopted a follow-up design and convenience sampling. Thirty-three subjects completed the questionnaire, and their HRV indices were measured.Findings: Patients' psychiatric symptoms showed a significant downward trend after hospitalization (P = .003). The standard deviation of the normal-to-normal inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…In previous studies of patients with schizophrenia in acute psychiatric wards, 84.85% of patients took their medicine regularly before hospitalization. 40 The proportion of patients who had taken their medicine regularly during the preceding month was slightly higher in the present study than that in previous studies.…”
Section: Resultscontrasting
confidence: 76%
“…In previous studies of patients with schizophrenia in acute psychiatric wards, 84.85% of patients took their medicine regularly before hospitalization. 40 The proportion of patients who had taken their medicine regularly during the preceding month was slightly higher in the present study than that in previous studies.…”
Section: Resultscontrasting
confidence: 76%
“… 50 Another study by Wang et al found that SDNN was significantly associated with increased aggression in hospitalized patients with schizophrenia, suggesting utility in HRV as a monitoring tool for inpatient episodes of both verbal and physical aggression. 51 Prognosis and prediction of symptom severity in patients with schizophrenia remains a current limitation that clinicians face while managing acute inpatient episodes, as well as preventing future episodes. As discussed previously in the management of patients with depression and PTSD, HRV may also be useful in monitoring treatment response in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…During a traditional, nonwearable biofeedback paradigm consisting of multiple on-site sessions, patients are trained to regulate their physiological reactions by consciously alternating their responses to the given feedback. Rapid developments in noninvasive, wearable technology (eg, breast bands, wrist sensors, smart fibers, and interactive textiles) have opened opportunities for biocueing, which combines real-time measurement in everyday life and just-in-time behavioral support [ 27 - 29 ].…”
Section: Introductionmentioning
confidence: 99%